Complex fibroadenoma with focal ossification- an enigmatic finding in a less common tumor - Hota, Subhransu Kumar; Giri, Ranjana; Kabra, Hardik; Chauhan, Devika; Pradhan, Prita; Pujari, Pran Singh (International Surgery Journal, 2021)
Breast lumps have diverse causes including benign as well as malignant lesions. Fibroadenoma (FA) is a common cause of breast lump. Complex fibroadenomas, a particular subtype, pose diagnostic dilemmas due to confusing the radiological findings and hold higher incidence of transformation to malignancy. A 49 year old female presented with a painless lump in right breast for 2 years which appeared calcified on radiology. Excision biopsy was performed which grossly revealed an encapsulated grey-white firm to hard with cystic areas. Microscopically the sections showed a well encapsulated fibroepithelial tumor showing areas of sclerosing adenosis, hyalinization, cysts lined by cuboidal cells with eosinophilic secretions, areas of calcification and ossification. No evidence of lobular hyperplasia or in-situ carcinoma was seen. Patient was advised follow up. This case represents the unusual occurrence of complex fibroadenoma in a middle-aged female showing with ossification.